Given that p^2+6p=q^2+6q and that p is not equal to q,

Find values of:

a. p+q

b. 4(p+q)^2

### 2 Answers | Add Yours

Given

`p^2+6p=q^2+6q`

`` So we can write

`p^2-q^2+6p-6q=0`

`(p-q)(p+q)+6(p-q)=0`

`(p-q)(p+q+6)=0`

since `p!=q =>p-q!=0` ,therefore

(1)

`p+q+6=0`

`p+q=-6`

(2)

`4(p+q)^2=4(-6)^2`

`=4xx36`

`=144`

Ans.

we can re-wrtite it as:

`p^2-q^2=6q-6p`

`(p+q)(p-q)=-6(p-q)`

semplifing:

`p+q= -6`

`4(p+q)^2=4(-6)^2= 144`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes